KONSTRUK PEMIKIRAN AL-GAZALI - Chairul Wahid Septialana; Irawan Irawan; Popi Puadah; Suhaeni . (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2021)
This study aims to enable the reader to know, understand, and moreover be able to implement the thoughts of al-Ghazali about the study of philosophical epistemology in the general sense of being used to refer to the various questions that arise and arise in the human mind about the difficulties encountered, and try to find answers and the right solution to believe. about understanding Philosophy, when calling it a name of science in the most general sense. And in the Islamic world there is also someone who developed this theory and his name is al-Farabi or Abu Nashr al-Farabi which says